Oxygen uptake kinetics: An underappreciated determinant of exercise performance - Jones, A. M.; Burnley, M. (International Journal of Sports Physiology and Performance, 2009)
The rate at which VO2 adjusts to the new energy demand following the onset of exercise strongly influences the magnitude of the "O2 deficit" incurred and thus the extent to which muscle and systemic homeostasis is perturbed. Moreover, during continuous high-intensity exercise, there is a progressive loss of muscle contractile efficiency, which is reflected in a "slow component" increase in VO2. The factors that dictate the characteristics of these fast and slow phases of the dynamic response of VO2 following a step change in energy turnover remain obscure. However, it is clear that these features of the VO2 kinetics have the potential to influence the rate of muscle fatigue development and, therefore, to affect sports performance. This commentary outlines the present state of knowledge on the characteristics of, and mechanistic bases to, the VO2 response to exercise of different intensities. Several interventions have been reported to speed the early VO2 kinetics and/or reduce the magnitude of the subsequent VO2 slow component, and the possibility that these might enhance exercise performance is discussed.